An Analysis Of Health Education Toward Mothers’ Attitude In Feeding Children Under Five With Malnutrition. - Susiani Endarwati; Dedi Saifulah (Journal of Health Science Community, 2025)
Malnutrition cases among children under five are still big challenge in Indonesia. It can be serious problems especially among children in between 6-24 months because it is the gold period of growth. Data from Health Ministry of Indonesia Republic shows that a prevalence of children under five with less and bad of nutrient status is still high although many interventions have been done. One of the reasons is the behavior and attitude of mothers in feeding their children such as eating frequency, food variety and quality of food that given to the children. The objective of this research is to know the impact of health education toward mothers’ attitude in feeding their children under five with malnutrition in Malang Regency. This research uses Pre-Experimental method by using one group pre test-post test design. Based on purpose sampling technique, it is got 71 mothers who have children under five with lack of nutrient as sampling. The independent variable is health education, and dependent variable is mothers’ attitude in feeding their children under five with malnutrition. Data collecting uses questionnaire, and data analysis is done by using paired sample t-test. It is shown p = 0.001<0.05, so the hypothesis is accepted. It means that there is an impact of health education toward mothers’ attitude in feeding their children who suffer lack of nutrient. This research shows the significant impact of giving health education toward mothers’ attitude in feeding their children with malnutrition. Therefore, it is need to use variety of media in promoting health education as interesting as possible such as video to improve mothers’ knowledge and understanding so they can give much contribution in preventing malnutrition cases among children under five.